Analisis Keberlanjutan Ekowisata Bahari Kategori Pantai Pantai Gua Manik dan Benteng Portugis di Kabupaten Jepara - Rojana, Ahmad Rifqi Faqih; Muhsoni, Firman Farid (Universitas Trunojoyo Madura, 2021)
Marine ecotourism is a type of tourism activities related to the ocean including in coastal areas, above sea level and below sea level. Donorojo subdistrict has many coastal ecotourism that is used as a vacation destination as well as learning about science. This study aims to find out the sustainability status of coastal ecotourism and coastal ecotourism management strategy in Banyumanis Village, Donorojo District, Jepara Regency. The method used by this research were qualitative method and sustainability analysis using Rapfish. The value of sustainability status of the ecological dimension of Gua Manik beach was 84.62 (sustainable) and Benteng Portugis beach was 72.91 (quite sustainable). The economic dimension value of Gua Manik beach was 46.79 (less sustainable) and Benteng Portugis beach was 48.99 (less sustainable). The value of the social and cultural dimensions of Gua Manik beach was 66.45 (quite sustainable) and on Benteng Portugis beach was 44.13 (less sustainable). The value of the legal and institutional dimensions of Gua Manik beach was 40.89 (less sustainable) and Benteng Portugis beach was 43.69 (less sustainable). The overall sustainability status of Gua Manik and Benteng Portugis was 47.25 (less sustainable).